Pengujian Kinerja Mesin Pencetak Keripik Tempe Sistem Pneumatik - Bambang Sugiyanto; Abdi Hanra Sebayang; Joko Kusmanto (Universitas Teuku Umar, 2023)
Tempe is a typical Indonesian food which is widely consumed by the public as a side dish to increase appetite, as well as as a snack that has its own flavor for its fans. Tempe artisans in Karanganyar Village, Secanggang District, Langkat Regency, North Sumatra Province, still maintain the method of making tempe chips by printing tempe one by one while it is still dough. typical. This is done because connoisseurs of tempe chips, especially their customers, state that tempe chips printed individually from the dough will have a distinctive taste The research was carried out by designing a tempe chip printing machine with a pneumatic system to control all mechanical movements of the machine and test the performance of the machine after the machine was built. The results of machine testing show that the machine can operate and the pneumatic system functions properly, the pneumatic pressure to move the dough scraper/leveler ranges from 0.9 to 1.0 bar, while the pneumatic pressure to open and close the dough pouring door above the mold ranges from 1.2 up to 1.5 bar, the operating capacity is up to 40 prints per hour or 400 sheets (plates) of tempe chips per hour.